Karakteristik Mekanik Komposit Poliester Berpenguat Serat Sisal Yang Diekstrak Dengan Metode Dekortikasi Dicetak Teknik Vacuum - Aryayustama, Komang Ghosagotama; Nindhia, Tjokorda Gde Tirta; Surata, I Wayan (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstractt Compositesl are a lcombinationl of two or lmore materials, land can replace metals because they are lightweight, non-corrosive, cost-effective, and easy to process. The printing process uses a vacuum technique because it can remove trapped voids in the resin. In this case, research and manufacture of natural fiber reinforced composites is carried out which is expectedl to be able to lcompetel with metal.This study used sisal leaf fiber extracted by decortication method and used a Yukalac C-108B polyester matrix with the addition of 1% MEKPO as a catalyst. Then given NaOH treatment 5% within 2 hours. Furthermore, composite printing was carried out using the Vacuum technique with variations in fiber weight fraction of 0%, 1%, 2%, 3%, and 4% random fiber orientation with a fiber length of 3 cm. The composite cuts conform to ASTM D638 standards for tensile tests and ASTM D790-02 for flexural tests.Thel tensile strengthl ofl the sisal lfiberl reinforced polyesterl composite extracted by the decortication method was highest at 0% fiber weight fraction with an average value of 39.37 MPa and the lowest was 12.27 MPa at 4% fiber weight fraction. Meanwhile, the highest composite flexural strength of 97.49 occurred at 0% fiber weight fraction and decreased by 56.35 MPa at 1% fiber weight fraction then continued to decrease lwith increasingl fiber lweight lfraction 2% andl 3% and peaked at 4%l fiber weightl fraction. with a flexurall strengthl value of 27.64 MPa Keywords: sisal leaves fiber, vacuum, tensile strength, flexural strength